Elective genomic screening: results of the implementation of a whole genome sequencing program at a medical check-up unit in Spain - Palao, Bibiana; Leon-Otegui, Miriam; Bernad, Raquel; Moreno-Coca, Maria; Ordoñez, Elena; Góngora, Elena; Castilla, Isabel; Sogbe, Miguel; Beloqui, Oscar; Patiño-García, Ana; Cirigliano, Vincenzo; Izquierdo, Luis (Frontiers in Genetics, 2026)
Elective Genomic Testing (EGT) can identify individuals at risk for actionable conditions that would not come to clinical attention following current testing guidelines. We describe the results of a checkup unit from a leading Spanish University hospital (Clínica Universidad de Navarra, Spain) that has incorporated EGT to their regular clinical practice. Medical anamnesis, biochemistry, low-intensity whole body scan and EGT with interpretation of over 560 genes related to actionable adult-onset diseases (Veritas Intercontinental, Spain) was performed in 400 participants, including medical consultation before and after the checkup. Clinically relevant variants were identified in 79/400 participants (19.8%). Thirteen individuals (3.3%) presented with clinical variants included in the American College of Medical Genetics and Genomics secondary finding list (ACMG SF list); 69.2% of these variants showed potential association with personal or family history (PFH). The study presents the results of the first hospital integrating EGT into the checkup unit.